2015
DOI: 10.1186/s12906-016-0992-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic and anti-oxidant potential of aged garlic extract (AGE) in streptozotocin-induced diabetic rats

Abstract: BackgroundAlthough aged garlic extract (AGE) shares some active components with fresh garlic and in spite of its palatability and milder side effects, the anti-diabetic and related anti-oxidant properties of AGE have not been investigated extensively, and the reported findings are inconsistent.This study investigated the anti-diabetic effects of 3 incremental doses of AGE in streptozotocin (STZ)-induced diabetic rats (fasting blood sugar > 20 mM).MethodDiabetic rats were divided into a control diabetic group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 45 publications
9
79
0
1
Order By: Relevance
“…34 Ajoene, a breakdown product of allicin, induce apoptosis, decrease lipid accumulation in adipocytes and increase thermogenesis. 34,35 Safety and tolerability Both AGE and amlodipine were well tolerated during the study and no new safety concerns were observed that were not known to occur with individual drug therapies. As shown in Table 3, total of four (13.3%) patients in group I and six (20%) patients in group II reported adverse drug reactions.…”
Section: Body Weight and Bmimentioning
confidence: 96%
“…34 Ajoene, a breakdown product of allicin, induce apoptosis, decrease lipid accumulation in adipocytes and increase thermogenesis. 34,35 Safety and tolerability Both AGE and amlodipine were well tolerated during the study and no new safety concerns were observed that were not known to occur with individual drug therapies. As shown in Table 3, total of four (13.3%) patients in group I and six (20%) patients in group II reported adverse drug reactions.…”
Section: Body Weight and Bmimentioning
confidence: 96%
“…8 Allium sativum L. (Liliaceae) commonly called garlic is used in modern folkloric medicine, as well as a spice for the treatment of many ailments. [9][10][11] Garlic, has been recognized to have a potential medicinal value due to its active constituents alliin (~0.8%) and allicin (∼3.7 mg/g) and is used as antifungal, antibacterial, antiviral, anti-helmintic, anti-inflammatory and antiseptic. 12 Moreover, reported literature indicates that garlic extracts exhibit activities against both gram negative and gram positive microbes all of which are cause of morbidity worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Adminstration of queous extract of A. sativum to induced diabetic rats reduced the blood glucose level, total serum lipids and cholesterol (Thomson et al, 2007;Ozougwu and Eyo, 2010;Badole et al, 2013;Thomson et al,2016).…”
Section: Allium Sativummentioning
confidence: 99%